Effects of carbon emission trading schemes on green technological innovation by industrial enterprises: Evidence from a quasi-natural experiment in China - Jingyin Liu; Xiao Liu (Journal of Innovation & Knowledge (JIK), 2023)
To mitigate global climate change and achieve the targets of the Nationally Determined Contributions (NDCs), the Chinese government implemented a carbon emission trading scheme (ETS) pilot policy in batches. However, there has been no unified consensus at present on whether the ETS pilot policy has stimulated green technological innovation. By applying a multi-period propensity score matching and difference-in-differences method, as well as using panel data from 2007-2019 of A-share listed Chinese firms, this study constructed a quasi-natural experiment to examine the causal effects of China's ETS pilot policy on the green technological innovation of the firms. The results were validated after a series of robustness checks and showed that the ETS has significantly encouraged green technological innovation in industrial enterprises. This positive effect is greater for firms with large capital scales, with better corporate governance, especially for those in the mining and manufacturing industry. Further analysis indicated that corporate social responsibility and operating income were the driving factors of the effects on innovation, whereas R&D expenditures have inhibited the effects.
Keywords: 650; Carbon emission trading scheme; Green technological innovation; Influencing mechanism; Multi-period PSM-DID